2020
DOI: 10.7861/clinmed.2019-0445
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant strategies for the patient with chronic kidney disease

Abstract: Chronic kidney disease (CKD) is a global health problem affecting up to 14% of the adult population in developed countries. On the basis of current guidelines, patients with CKD will often fulfi l criteria for both short-term and long-term anticoagulation. Paradoxically, patients with CKD are not only at a higher risk of thrombosis, they are also at increased risk of bleeding. Furthermore, the pharmacokinetics and pharmacodynamics of many anticoagulant therapies are signifi cantly affected by renal dysfunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…When clinical practice guidelines recommend warfarin therapy in patients with CKD, it is suggested that drug dose adjustment is not necessary because warfarin is eliminated by hepatic metabolism [17,20]. However, considering warfarin's narrow therapeutic window and its susceptibility to multiple drug and food interactions, interpretation of dose adjustment solely on the basis of estimated glomerular ltration rate (eGFR) may be an over-simpli ed approach under uremia and downregulation of CYP450 in these patients [11,21]. In fact, several clinical studies have shown that patients with CKD require lower warfarin dosages to maintain therapeutic anticoagulation compared to patients with normal kidney function [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When clinical practice guidelines recommend warfarin therapy in patients with CKD, it is suggested that drug dose adjustment is not necessary because warfarin is eliminated by hepatic metabolism [17,20]. However, considering warfarin's narrow therapeutic window and its susceptibility to multiple drug and food interactions, interpretation of dose adjustment solely on the basis of estimated glomerular ltration rate (eGFR) may be an over-simpli ed approach under uremia and downregulation of CYP450 in these patients [11,21]. In fact, several clinical studies have shown that patients with CKD require lower warfarin dosages to maintain therapeutic anticoagulation compared to patients with normal kidney function [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Despite these advantages of NOACs over VKAs, NOAC therapy requires caution in patients with CKD. Although varying in degrees, all NOACs are dependent on the kidney for elimination, so their use makes dose adjustment mandatory in patients with CKD [11,32]. Unfortunately, there is no standardized test for monitoring NOACs to con rm maintenance of therapeutic anticoagulation in these patients after dose adjustment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, renal failure is common in acute COVID-19. Thus, heparins, especially unfractionated heparin, are a safer anticoagulation choice due to DOACs' renaldependent metabolism (40). Furthermore, heparin binds to COVID-19 spike proteins and IL-6, which are elevated in COVID-19 patients (41).…”
Section: Are Doacs An Option For Anticoagulation In Covid-19 Hospital...mentioning
confidence: 99%
“…Compared to the general population, advanced CKD patients are at an increased risk of Atrial Fibrillation (AF) and Venous Thromboembolism (VTE), warranting short and long-term anticoagulation treatment [4][5][6]. Advanced CKD patients are also at an increased risk of bleeding, making it difficult to choose an optimal anticoagulant agent for this population [5].…”
Section: Introductionmentioning
confidence: 99%